Characterisation by multilocus sequence and porA and flaA typing of Campylobacter jejuni isolated from samples of dog faeces collected in one city in New Zealand. Issue 4 (4th July 2017) - Mohan, V; Stevenson, MA; Marshall, JC; French, NP
Abstract: AIMS: To investigate the prevalence of Campylobacter spp. and C. jejuni in dog faecal material collected from dog walkways in the city of Palmerston North, New Zealand, and to characterise the C. jejuni isolates by multilocus sequence typing (MLST) and por A and fla A antigen gene typing. METHODS: A total of 355 fresh samples of dogs faeces were collected from bins provided for the disposal of dog faeces in 10 walkways in Palmerston North, New Zealand, between August 2008–July 2009. Presumptive Campylobacter colonies, cultured on modified charcoal cefoperazone deoxycholate plates, were screened for genus Campylobacter and C. jejuni by PCR. The C. jejuni isolates were subsequently characterised by MLST and por A and fla A typing, and C. jejuni sequence types (ST) were assigned. RESULTS: Of the 355 samples collected, 72 (20 (95% CI=16–25)%) were positive for Campylobacter spp. and 22 (6 (95% CI=4–9)%) were positive for C. jejuni . Of the 22 C. jejuni i solates, 19 were fully typed by MLST. Ten isolates were assigned to the clonal complex ST-45 and three to ST-52. The allelic combinations of ST-45/ fla A 21/ por A 44 (n=3), ST-45/ fla A 22/ por A 53 (n=3) and ST-52/ fla A 57/ por A 905 (n=3) were most frequent. CONCLUSIONS: The successful isolation of C. jejuni from canine faecal samples collected from faecal bins provides evidence that Campylobacter spp. may survive outside the host for at least several hours despite requiring fastidious growth conditions in culture. The results show that dogs carry C. jejuni genotypes (ST-45, ST-50, ST-52 and ST-696) that have been reported in human clinical cases. CLINICAL RELEVANCE: Although these results do not provide any evidence either for the direction of infection or for dogs being a potential risk factor for human campylobacteriosis, dog owners are advised to practice good hygiene with respect to their pets to reduce potential exposure to infection.